Langganan Digital: Tinjauan Hukum Islam terhadap Perpanjangan Otomatis Aplikasi pada Generasi Z - Elsa Silvia Nur Aulia; Cecep Alba; Asep Wawan Jatnika; Sansan Ziaul Haq (Fakultas Seni Rupa dan Desain ITB, 2026)
The rapid growth of digital subscription services has normalized auto-renewal mechanisms, particularly among Generation Z. However, this convenience often leads to passive consumption and unintentional financial deductions. This study aims to analyze the practice of autorenewal in digital subscriptions among Gen Z from both socio-technological and Islamic legal (fiqh muamalah) perspectives. Employing a quantitative descriptive approach, data were collected from 50 Gen Z respondents in Bandung through questionnaires. The findings reveal a high subscription rate (74%), yet a significant disconnect exists: 40% of users infrequently utilize the services they continue paying for, and 24% are unaware of active autorenewals. From a socio-technological view, platforms exploit user inertia, leading to a